2023
DOI: 10.1002/solr.202300727
|View full text |Cite
|
Sign up to set email alerts
|

Novel Interlayer Boosting the Performance of Evaporated Cu2O Hole‐Selective Contacts in Si Solar Cells

Gabriel Bartholazzi,
Mohamed M. Shehata,
Rabin Basnet
et al.

Abstract: Passivating contacts based on transition metal oxides are of great interest for applications in crystalline silicon (c‐Si) solar cells due to their improved optical transparency and potential cost reduction. In this work, the contact resistivity and passivation for thermally evaporated Cu2O are investigated and optimized, with and without an Al2O3 interlayer, as a hole‐selective contact to c‐Si. Additionally, we implement an Al y TiO x /TiO2 stack as a novel passivating tunnel interlayer for hole‐selective con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This new film stack also exhibited better thermal stability, with ρ c decreasing as the deposition temperature increased, attributed to ZnO's lower bulk resistivity and higher carrier mobility and concentration. 43 Additionally, Bartholazzi et al 44 applied the Al y TiO x /TiO 2 stack as an interlayer to enhance hole selectivity in Cu 2 O. They found that by reducing the thickness of the stack to allow the transport of holes through tunneling, the work function of Cu 2 O increased from 4.63 to 4.74 eV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This new film stack also exhibited better thermal stability, with ρ c decreasing as the deposition temperature increased, attributed to ZnO's lower bulk resistivity and higher carrier mobility and concentration. 43 Additionally, Bartholazzi et al 44 applied the Al y TiO x /TiO 2 stack as an interlayer to enhance hole selectivity in Cu 2 O. They found that by reducing the thickness of the stack to allow the transport of holes through tunneling, the work function of Cu 2 O increased from 4.63 to 4.74 eV.…”
Section: Introductionmentioning
confidence: 99%
“…This new film stack also exhibited better thermal stability, with ρ c decreasing as the deposition temperature increased, attributed to ZnO's lower bulk resistivity and higher carrier mobility and concentration. 43 Additionally, Bartholazzi et al 44 To date, the highest efficiency achieved by c-Si solar cells using a TiO x -based electron-selective contact is 23.1%. This was accomplished with a partial rear contact configuration, where the rear side was predominantly passivated by SiN x , with small openings that allow a TiO x /LiF x /Al stack to contact the n-Si.…”
Section: Introductionmentioning
confidence: 99%